Pengaruh Emotional Focused Coping terhadap Stress Akademik pada Siswa Kelas XII SMA Muhammadiyah 3 Padang - Larashati, Larashati; Mahbubah, Hanik Faizatul; Rizal, Salsabila Az-Zahra; Murti, Varadina Dwi (TSAQOFAH, 2025)
Stress that occurs in education is often known as academic stress. This academic stress can occur at all levels of education, including kindergarten, elementary school, junior high school, high school, and university. Academic stress occurs because of the pressure felt by students with the emergence of stressors related to academics. Students who are in class XII SMA are one of the most closely related to academic stress, they are faced with the choice to continue their education in college which will determine their future. Stress experienced by students can be overcome to help regulate emotions that arise when stress is experienced, emtional focused coping can be a way to relieve stress. This study aims to see the effect of emotional focused coping on academic stress in XII grade students of SMA Muhammadiyah 3 Padang. The type of research conducted is quantitative research with non-parametric statistical methods Normality test using Kolmogorov-Smirnov. The sample in this study were all XII grade students of SMA Muhammadiyah 3 Padang, where data collection used an academic stress scale and an emotional focused coping scale in the form of a questionnaire distributed via QR Code and WhatsApp groups of XII grade students. Significant results are at 0.056 which indicates that there is an influence between Emotional Focused Coping on Academic Stress in XII grade students of SMA Muhammadiyah 3 Padang. Based on the results of the analysis, it can be seen that XII grade students of SMA Muhammadiyah 3 Padang have the ability of emotionally focused coping strategies to resolve academic stress.